Electrophysiological study generally is negative in patients < 40 years suspected of supraventricular tachycardia but also complaining of chest pain and/or syncope. (15th January 2016) - Brembilla-Perrot, Béatrice; Sellal, Jean Marc; Olivier, Arnaud; Villemin, Thibaut; Manenti, Vladimir; Brembilla, Alice; Rizk, Joseph; Chillou, Christian De; Moulin-Zinsch, Anne; Marçon, François; Girerd, Nicolas
Abstract: Background: The diagnosis of paroxysmal supraventricular tachycardia (SVT) frequently is a dilemma. Electrophysiological study (EPS) is the only means to evaluate the nature of symptoms when noninvasive studies remain negative. Our objectives were to determine the clinical factors of negativity or positivity of (EPS) in patients suspected of SVT. Methods: EPS was performed in 2650 patients complaining of tachycardia and suspected of SVT. Transesophageal EPS consisted of programmed atrial stimulation in control state and after isoproterenol. Patients were followed from 1 month to 18 years (2.93 ± 4 years). Results: SVT was induced in 1944 patients, age 48 ± 19.5. EPS remained negative in 706 patients, age 34 ± 17 (p < 0.0001). Age < 40 years, feeling of dizziness/syncope or chest pain associated with tachycardia, the absence of heart disease or short PR interval was more frequent in patients with negative EPS (respectively 64, 42, 26, 96, 88.5%) than in patients with induced SVT (34, 14, 4, 88, 59%) (p < 0.0001).The positive predictive value for the prediction of a negative EPS of age < 40, chest pain, syncope or their association was 63.5, 42, 26.5, 11% and negative predictive value was 66, 86, 94.5, 99.5%. At multivariate analysis, age < 40 (0.000, OR 2.79), the presence of syncope associated with tachycardia (0.000, OR 5.075) or chest pain (0.000, OR 17.923) was an independent factor of negative EPS. Conclusions: Among patients complaining of nondocumented tachycardia, suspected of SVT, the association of tachycardia with chest pain and/or syncope and age < 40 years generally was correlated with a negative EPS and did not indicate initially invasive studies. In the remaining patients transesophageal EPS is indicated. Highlights: In patients < 40 years, with chest pain and syncope, transesophageal EPS is recommended. To evaluate the nature of tachycardia To detect masked preexcitation To predict a low risk of SVT and AF in patients with negative EPS The more the patient is aged, the more the probability of having a positive EPS is high.